Amination of meso‐Bromoporphyrins and 9‐Haloanthracenes with Diarylamines Catalyzed by a Palladium–PEPPSI Complex. Issue 12 (2nd October 2013) - Suzuki, Yuko; Fukui, Norihito; Murakami, Kei; Yorimitsu, Hideki; Osuka, Atsuhiro
Abstract Palladium‐catalyzed aminations of bulky aryl halides such as meso‐bromoporphyrins and 9‐haloanthracenes with diarylamines provided efficient syntheses of meso‐aminoporphyrins and 9‐aminoanthracenes. Commercially available and air‐stable Pd‐PEPPSI complexes that have N‐heterocyclic carbene (NHC) as ligands have the highest catalytic activities. The scope of diarylamines is wide enough to use diphenylamine, phenoxazine, phenothiazine, 9, 10‐dihydroacrydine, and carbazole.